2002
DOI: 10.1590/s0100-06832002000100015
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade e absorção de fósforo por plantas de milho em função de doses e modos de aplicação de adubo fosfatado em solo de tabuleiro costeiro

Abstract: RESUMOO objetivo deste estudo foi avaliar os efeitos de doses e modos de aplicação de P ao solo sobre a absorção e a eficiência de utilização do P foliar e a produtividade de milho (Zea mays) cultivado em um Argissolo Amarelo, característico dos tabuleiros costeiros. Avaliaram-se as doses de 0, 45, 90, 135 e 180 kg ha -1 de P 2 O 5 , distribuídas no sulco de plantio ou a lanço. O experimento foi realizado na estação chuvosa, de junho a setembro de 1998, no Campo Experimental de Umbaúba (Embrapa Tabuleiros Cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
10

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 8 publications
1
7
0
10
Order By: Relevance
“…Outros fatores devem ser do conhecimento do técnico e/ou agricultor, para que conduzam a um melhor uso dos adubos (BARRETO;FERNANDES, 2002;LACERDA et al, 2006). Em solos com acidez elevada e baixa disponibilidade de P, a aplicação de calcário e de fertilizantes fosfatados é fundamental para a obtenção de altas produtividades (ERNANI et al, 2001).…”
Section: Introductionunclassified
“…Outros fatores devem ser do conhecimento do técnico e/ou agricultor, para que conduzam a um melhor uso dos adubos (BARRETO;FERNANDES, 2002;LACERDA et al, 2006). Em solos com acidez elevada e baixa disponibilidade de P, a aplicação de calcário e de fertilizantes fosfatados é fundamental para a obtenção de altas produtividades (ERNANI et al, 2001).…”
Section: Introductionunclassified
“…On the other hand, Barreto & Fernandes (2002) confirmed that broadcast application with incorporation into the soil of triple superphosphate increased corn production in the Ultisol, by comparison with the localized application of this fertilizer. This apparently conflicting result is related to the low P absorption capacity of the soil studied by these authors, allowing a higher P uptake owing to the increased root contact with the fertilizer, with no significant increase in P-fixation.…”
Section: Resultsmentioning
confidence: 62%
“…Phosphorus deficiency can also reduce the synthesis of nucleic acids and protein, inducing accumulation of soluble nitrogen compounds in the tissue, slowing cellular growth and consequently causing a delay in leaf emergence and a reduction in the sprouting and development of secondary roots, as well as in dry matter production and yield (Grant et al, 2001). Barreto and Fernandes (2002) evaluated corn yield as a function of increasing levels of phosphorus applied to the soil and observed increases of over 50% in grain yield.…”
Section: Resultsmentioning
confidence: 99%